2019
DOI: 10.1186/s12885-019-6364-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lymph node dissection on stage-specific survival in patients with upper urinary tract urothelial carcinoma treated with nephroureterectomy

Abstract: BackgroundWe aimed to estimate the stage-specific impact of lymph node dissection (LND) on survival for upper urinary tract urothelial carcinoma (UTUC) patients treated with nephroureterectomy (NU).MethodsOverall, 7278 UTUC patients undergoing NU within the SEER database from 2004 to 2015 were identified. Kaplan-Meier plots illustrated overall survival (OS) and cancer-specific survival (CSS) rates according to LND status. Multivariable Cox regression analyses assessed the effect of LND on OS and CSS rates stra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…Similarly, the disease-specific survival (DSS) rates were 72.1 vs. 29.8% (HR = 2.9; 1.47–6.01) and overall survival (OS) rates were 66 vs. 22.3% (HR = 2.97; 1.47–6.01). In another study conducted among preoperatively node-negative patients, CSS and OS rates were higher in pN0 patients compared to those with pNx and pN1–3 disease, and these results were consistent across all tumor stages ( 33 ). Thus, pN+ patients' harbor decreased survival rates compared to pN0, highlighting the negative prognostic impact of lymph node involvement.…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Similarly, the disease-specific survival (DSS) rates were 72.1 vs. 29.8% (HR = 2.9; 1.47–6.01) and overall survival (OS) rates were 66 vs. 22.3% (HR = 2.97; 1.47–6.01). In another study conducted among preoperatively node-negative patients, CSS and OS rates were higher in pN0 patients compared to those with pNx and pN1–3 disease, and these results were consistent across all tumor stages ( 33 ). Thus, pN+ patients' harbor decreased survival rates compared to pN0, highlighting the negative prognostic impact of lymph node involvement.…”
Section: Methodsmentioning
confidence: 63%
“…The indication of LND and its extent must be discussed as the impact of lymphadenectomy itself on survival is to be proven. Zhai et al studied the effect of LND during RNU on cancer-specific survival and overall survival ( 33 ). They retrospectively analyzed 7,278 patients from SEER database with histologically proven UTUC, who underwent RNU with or without LND.…”
Section: Methodsmentioning
confidence: 99%
“…Nodal dissection has a controversial therapeutic role, and the procedure is performed if nodal metastasis is defined in the clinical image. Dominguez-Escrig et al, Don et al, and Zhai et al reported that LND had a survival benefit in patients with high stage (≥pT2) UTUC and reduced the risk of local recurrence [22][23][24]. Guo et al demonstrated that LND during RUN provides more accurate pathological staging and prediction of prognosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 4 ] The reported 5-year recurrence-free survival (RFS) and cancer-specific survival (CSS) rates are 50% to 80% and 70% to 74.4%, respectively. [ 5 7 ] Great efforts have been made to improve the understanding of UTUC, but the management for UTUC still remains a big challenge. These unfavorable results highlight the importance of developing a therapeutic strategy to improve the prognosis of UTUC.…”
Section: Introductionmentioning
confidence: 99%